(untitled) (Research, Society and Development, 2024)
Several studies have explored the benefits and safety strategies related to resistance training in children and adolescents. Despite this, their integration into school physical education classes is still limited. The analysis of current scientific evidence on this topic can contribute to a better understanding of the pedagogical potential of resistance training and facilitate its implementation in the school environment. In this context, the present review study aimed to synthesize the scientific findings related to the benefits of resistance training in schoolchildren when incorporated as content in the curricular component of School Physical Education. The search was carried out in electronic databases such as Google Scholar, PubMed, Virtual Health Library (BVS) and SciELO, using combinations of terms associated with resistance training, adolescents and school. 08 articles were identified, including field studies and reviews, published in the period from 2019 to 2023. The results highlighted a number of benefits associated with the supervised practice of resistance training, such as improvements in physical fitness, body composition, and biochemical indicators, as well as contributions to the correction of postural deviations and the reduction of the risk of injuries and diseases related to a sedentary lifestyle. In addition, there was an increase in students’ motivation and adherence to physical education classes. The findings suggest that resistance training, when conducted with adequate supervision, can offer multiple benefits to the health and engagement of students, reinforcing its relevance as pedagogical content for the school environment.